Analysis of T and NK cell subsets in the Sicilian population from young to supercentenarian: The role of age and gender. (17th June 2021) - Ligotti, Mattia Emanuela; Aiello, Anna; Accardi, Giulia; Aprile, Stefano; Bonura, Floriana; Bulati, Matteo; Gervasi, Francesco; Giammanco, Giovanni M; Pojero, Fanny; Zareian, Nahid; Caruso, Calogero; Farzaneh, Farzin; et al.
Summary: Ageing dramatically affects number and function of both innate and adaptive arms of immune system, particularly T cell subsets, contributing to reduced vaccination efficacy, decreased resistance to infections and increased prevalence of cancer in older people. In the present paper, we analysed the age-related changes in the absolute number of lymphocytes in 214 Sicilian subjects, and in the percentages of T and natural killer (NK) cells in a subcohort of donors. We compared these results with the immunophenotype of the oldest living Italian supercentenarian (aged 111 years). The results were also sorted by gender. The correlation between number/percentage of cells and age in all individuals. and separately in males and females, was examined using a simple linear regression analysis. We did not record the increase in the rate of inversion of the CD4/CD8 ratio, frequently reported as being associated with ageing in literature. Our observation was the direct consequence of a flat average trend of CD4 + and CD8 + T cell percentages in ageing donors, even when gender differences were included. Our results also suggest that CD4 + and CD8 + subsets are not affected equally by age comparing females with males, and we speculated that gender may affect the response to cytomegalovirus (CMV) infection. The supercentenarian showed a unique immunophenotypic signature regarding the relative percentages of her T cell subsets, with CD4 + and CD8 + T cell percentages and CD4 + naive T cell values in line with those recorded for the octogenarian subjects. This suggests that the supercentenarian has a naive 'younger' T cell profile comparable to that of a >80-year-old female. Graphical Abstract: